Nanotechnology in Medical Therapeutics and Tissue Engineering - Sahu, Samir; Malla, Asish (International Journal of Psychosocial Rehabilitation, 2019)
Nanotechnology has developed to satisfy information technology industry requirements. Nanotechnology research has then grown to go into countless areas. The new technology has driven the development of different medical advancements including drug delivery systems, contrast agents for cancer treatment, diagnostic instruments, and tissue regeneration. In the beauty industry, nanotechnology has been implemented including the skincare market, dermal medicines, bleaching protocols. Minimal invasive approaches to surgical treatment by nanotechnological techniques created new horizons in plastic surgery. The use of nanotechnology has more widely affected the area of plastic and reconstructive surgery than have other medical sciences. Throughout various plastic and reconstructive surgery procedures, the results of nanotechnology could be detected, ranging through the use of nanomaterials throughout implantable materials to wound repair, wound healing and wound dressing, particularly in tissue engineering and regeneration. In the fields of tissue engineering and the regeneration the most exciting and fast advances are. The possibility of imitating physiological tissue to regenerate tissues and organs is a cutting-edge improvement. Successful and effective results obtained in these topics are actively creating new development opportunities.